Determining factors of foreign direct investment in Emerging Market Asia: A panel data analysis (2005-2020) - Anisa Dwi Ariyani; Firmansyah Firmansyah (Optimum: Jurnal Ekonomi dan Pembangunan, 2023)
Foreign Direct Investment (FDI) is recognized as a major force that integrates developing countries into the world economy and is expected to be a key factor in driving sustainable and balanced economic growth. Emerging Market Asia countries are the host countries that receive the highest inflows of Foreign Direct Investment (FDI) compared to other emerging market countries. Even in crisis conditions, emerging market countries, especially the Asian region, are still the destination for investment because of their resilience to crisis shocks. In analyzing the determinants of Foreign Direct Investment (FDI), the variables used are Market Size, Trade Openness, Interest Rates, Control of Corruption, Education Levels and Telecommunication Infrastructure. The analytical method used is the Fixed Effect Model (FEM) Data Panel. The results of the study show that market size, corruption control and telecommunications infrastructure have a positive and significant effect on foreign direct investment inflows. The Education Level variable was found to have a negative effect on FDI inflows. While the variables of Trade Openness and Interest Rates have no significant effect. The implications of this research are that host country governments need to create an investment-friendly environment with transparent bureaucratic conditions to increase the trust of foreign investors. Additionally, governments also need to provide facilities that can support the private sector in creating productive investments, such as by improving GDP performance and enhancing infrastructure quality.